A Review of Research on the Pillow Basalts of the Second Member of the Liushugou Formation in the Bogda Mountains - Wang, Senyu (International Journal of Natural Resources and Environmental Studies, 2026)
The Bogda orogenic belt, located in the eastern segment of the East Tianshan Mountains, is a key component of the Central Asian Orogenic Belt. Its Late Paleozoic tectonic evolution is closely related to the final closure of the Paleo-Asian Ocean. The Upper Carboniferous Liushugou Formation (C2l) is a widely distributed marine volcanic-sedimentary rock series in the Bogda region. The second lithological member (C2l²) is characterized by the development of typical pillow basalts and serves as an important window for exploring the Late Carboniferous tectonic attributes of this area and the timing of the Paleo-Asian Ocean closure. This paper systematically reviews the regional tectonic background, petrological and geochemical characteristics of the pillow basalts of the second member of the Liushugou Formation in the Bogda Mountains, with a focus on sorting out the main academic viewpoints, core debates, and controversial focal points regarding their tectonic setting. It also summarizes current research status both domestically and internationally, aiming to provide a reference for an in-depth understanding of the Late Paleozoic tectonic evolution of the southern margin of the Central Asian Orogenic Belt.